Development, physical, physical-chemical and sensory evaluation of fresh pasta enriched with Spirulina platensis: an alternative for infant feeding (Research, Society and Development, 2020)
The objective was to develop and evaluate the physical, physical-chemical and sensory parameters of fresh spaghetti type pasta, enriched with different concentrations of Spirulina platensis. For that, four formulations were produced with 0%, 5%, 10% and 15% Spirulina platensis. The physical, physical-chemical and sensory parameters were evaluated, the latter, being carried out with 53 untrained tasters, preschool and school compounds from the public school system of Curimataú Paraibano, aged between 4 and 9 years. In addition, an analysis was made of the percentage of protein enrichment in the formulations, based on the Dietary Reference Intakes (IDR) for each age group. The results referring to physical and physical-chemical evaluations showed that the replacement of part of the wheat flour by Spirulina platensis, reflects in the increase of the protein, lipid, ash and promotes reduction of the percentage of carbohydrates. According to the Dietary Reference Intakes, a portion (100g) of the masses plus Spirulina platensis provided the daily percentage of nutrients for children (ages 1-10 years) needed to be classified as enriched mass. All formulations presented their evaluation located in the “indifferent” score, showing that the formulation that contained 15% Spirulina platensis was the one that obtained the best percentage of acceptability reaching 60.37%. Therefore, it was found that the addition of Spirulina platensis, in pasta, spaghetti type, promotes a food with improved nutritional characteristics, easy to prepare, low cost and with good acceptability, which can be inserted as an alternative food in the diet of preschoolers and schoolchildren.